A CFA-Induced Model of Inflammatory Skin Disease in Miniature Swine - Nalú Navarro-Alvarez; Beatriz M. M. Gonçalves; Alec R. Andrews; David H. Sachs; Christene A. Huang (International Journal of Inflammation)
Similarities between porcine and human skin make the pig an ideal model for preclinical studies of cutaneous inflammation and wound healing. Complete Freund’s adjuvant (CFA) has been used to induce inflammation and to study inflammatory pain in several animal models. Here, we evaluated the inflammation caused by CFA injected in different layers of skin and subcutaneous (SC) tissue in a large-animal model. The degree of inflammation was evaluated at early and late time points by visual inspection and histopathologic analysis. In addition, the side effects of CFA injections were evaluated based on clinical findings, behavioral changes, physiologic state, and (histo)pathologic lesions. Pigs were injected with CFA at the back of the neck’s skin at different depths. All animals showed histologic signs of inflammation at the injection site. Animals injected SC did not show any signs of pain or distress (loss of appetite, abnormal behavior) and did not require pain medication. Inflammation was followed by measuring the area of induration beneath the skin. Animals injected into the dermis and/or epidermis demonstrated a severe inflammatory response on the skin surface with massive swelling, redness within 12hrs of CFA injection, and severe skin necrosis within a week, preventing accurate induration measurements. In contrast to animals injected SC, animals receiving intradermal and/or intraepidermal injection of CFA showed signs of distress requiring pain medication. Conclusion. SC injection of CFA in swine induces an inflammatory response that can be measured accurately by induration without causing unnecessary discomfort, providing a useful preclinical large-animal model of inflammatory skin disease.